Building a cell-factory in Crithidia fasciculata: a bio-sustainable system to produce high-value polyunsaturated fatty acids - Michela Cerone; Louise L. Major; Terry K. Smith (Microbial Cell Factories, 2025)
Abstract Fatty acids (FAs) are a class of diverse biomolecules that are essential for a wide variety of biological processes. Recently, ω-3 and ω-6 polyunsaturated FAs (PUFAs) have received a lot of attention for their benefit and essentiality to human health. Their demand is constantly increasing alongside the ever-decreasing availability of sources of natural PUFAs, such as some plants and marine ecosystems, which are now endangered by agribusiness and climate change. Most of the novel microbial synthetic platforms to produce ω-3 and ω-6 PUFAs (e.g. yeast, microalgae, oleaginous microorganisms, bacteria etc.) are costly. On the other hand, industrial processes based on chemical total synthesis of PUFAs is often challenging. Here, we propose an innovative and bio-sustainable method to make ω-3 and ω-6 PUFAs by building a cell-factory in Crithidia fasciculata, using genetic manipulation of endogenous FA desaturases and elongases, supplementation of the culture media with cheap sources of fats (such as used cooking oils), and culturing temperature reduction. In these unusual environments, C. fasciculata show high adaptability: the cells grow rapidly producing large biomass from small volumes of culture, scavenge and remodel unusual fat sources, as well as biosynthesising high value FAs and PUFAs de novo. By genetic manipulation, allowing overexpression of either the endogenous Δ6-desaturases or Δ4-desaturases, in conjunction with the endogenous elongase Elo4, high value ω-6 and ω-3 PUFAs were yielded to a maximum of 50% of the total FA content of the cells. These bioengineered C. fasciculata provide a low-cost and bio-sustainable platform to increase the production of essential PUFAs which can be introduced into the food chain at lower costs.